Redefining Translation Spaces in the Soviet Union: From Revisionist Policies to a Conformist Translation Theory - Dmitrienko, Gleb (TTR)

(untitled) (Association canadienne de traductologie, 2019)
Due to its manipulative potential and ability to create deliberate distortions, translation has become instrumental for many projects that involve culture and identity manipulations. In some political and social contexts, translation may serve as a driving force for deliberate and consistent intervention by power holders in order to modify and exploit the nation’s mindset, its cultures and identities for political purposes. For such manipulative strategies, translation becomes essential as it contributes to the propagation of a given ideology by conveying it in different languages, and aids in creating and sustaining a state-sponsored conformist identity. This paper analyzes such a case in relation to the evolution of Soviet translation and translatology in the context of a totalitarian state. By examining the role of translation in a series of forced cultural reorientations that are a part of Russian national history, we explore how translation was used to impose a supranational Soviet identity. We also present how the ongoing disputes surrounding translation policies and translation methods in the Socialist state resulted in the emergence of two opposing schools of thought: one that studied translation within the paradigms of structuralist linguistics, and the other that advocated for a literary approach. By framing our analysis of the Russian translatological discourse within the context of Soviet ideology and the rise of totalitarianism, we demonstrate how each of the schools manipulated the official state ideology in a struggle for recognition. We also seek to explain how linguistic structuralism came to represent the dominant theoretical framework for Soviet translation science, thus relegating to oblivion the “realist” approach to translation.